PENGARUH ROA, DER, CURRENT RATIO, DAN SIZE TERHADAP RETURN SAHAM DAN PBV (Students' Journal of Economic and Management, 2014)
This study aimed to examine the effect of ROA, DER, Current Ratio, Size on Stock Return and PBV. By using purposive sampling method, for populations company for 3 years (2009-2010) gained 107 members of the sample. The analysis technique using multiple regression analysis method previously performed tests of normality and classical assumption. In addition, this study also uses the F statistic test and the coefficient determination. The latter hypothesis test using the t test. The results showed that the variables ROA, DER, and Size positive and significant effect on Stock Return and Stock Return positive and significant effect on PBV. Meanwhile variables CR negative and no significant effect on Stock Return. Keyword: ROA, DER, Current Ratio, Size, Stock Return, and PBV